2008
DOI: 10.4028/www.scientific.net/msf.575-578.1038
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Accurate Control of Initial and Finishing Cooling Temperatures for X70 Pipeline Steels

Abstract: Different cooling parameters, including the initial cooling temperature, finishing cooling temperature and cooling rate, have a significant effect on the final microstructures and properties for pipeline steels. In present work, Gleeble-1500 thermal-mechanical simulator was used to investigate the microstructural evolution of X70 pipeline steels under different cooling conditions, and the microstructures obtained were analyzed using optical microscope and transmission electron microscope. The experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous investigations have revealed that the acicular ferrite grains with different sizes grow up in different directions. However, no direction is in the dominate place; the reticular boundary of the pre-existing austenite grains disappears gradually, while some of the quasi-polygonal grain boundaries get across the original austenite boundaries and randomly interlace apparently, so the order and the directions are in mess [7].This characteristic of AF contributes a lot to inhibit the crack propagation, and subsequently increased the toughness of X65MO base metal [8]. The high density of dislocation in AF (Fig.…”
Section: Inter-granular Corrosion Propertymentioning
confidence: 97%
“…Previous investigations have revealed that the acicular ferrite grains with different sizes grow up in different directions. However, no direction is in the dominate place; the reticular boundary of the pre-existing austenite grains disappears gradually, while some of the quasi-polygonal grain boundaries get across the original austenite boundaries and randomly interlace apparently, so the order and the directions are in mess [7].This characteristic of AF contributes a lot to inhibit the crack propagation, and subsequently increased the toughness of X65MO base metal [8]. The high density of dislocation in AF (Fig.…”
Section: Inter-granular Corrosion Propertymentioning
confidence: 97%